2008
DOI: 10.1088/0960-1317/19/1/015027
|View full text |Cite
|
Sign up to set email alerts
|

Analysis, simulation and fabrication of MEMS springs for a micro-tensile system

Abstract: The support spring of a uniaxial micro-tensile system for testing micro-scale thin films is studied in this paper. Stresses of different shape springs are analyzed with the finite element method (FEM). The simulated results show that the stress of an S-shaped spring is lower compared with a U-shaped spring with the same dimensions (100 μm thick, 100 μm wide, 250 μm inner diameter and 5 turns). The maximum stress of the S-shaped spring is about 133 MPa when the displacement of 100 μm is imposed at one end of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 17 publications
0
10
0
Order By: Relevance
“…Especially, the reported Young's modulus is much lower than 210 Gpa [15], [16]. A microtensile measuring method was developed by Rui Liu et al [17], [18], by which the samples fabricated in the same conditions as the microswitch were measured. Preliminary results show that the Young's modulus was around 100 Gpa.…”
Section: A Original Design With Compliant Bridge-type Beamsmentioning
confidence: 99%
“…Especially, the reported Young's modulus is much lower than 210 Gpa [15], [16]. A microtensile measuring method was developed by Rui Liu et al [17], [18], by which the samples fabricated in the same conditions as the microswitch were measured. Preliminary results show that the Young's modulus was around 100 Gpa.…”
Section: A Original Design With Compliant Bridge-type Beamsmentioning
confidence: 99%
“…For microserpentine investigation, Barillaro et al designed two types of serpentine springs and analyzed their spring constants for out-of-plane motion through theoretical analysis and numerical analysis by using the finite element method [22]. Liu et al discussed the stress and stiffness of S-shaped springs and reported that the number of turns of springs has a significant effect on their stress and stiffness [29]. Yeh et al found that serpentine springs can provide a larger rotating angle than the springs of clamped straight beams in comb drive actuators [30].…”
Section: Introductionmentioning
confidence: 99%
“…The optical images of the test chip and the specimen are shown in figures 1(k), (l). The design and fabrication details of the tensile test specimen are given in[11,12].…”
mentioning
confidence: 99%